Existential Crisis Reflected in Louis-Ferdinand Celine’s Journey to The End of The Night - Arianto, Rendy; Andayani, Ambar (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This study discusses the existential crisis that occurs in Louis-Ferdinand Celine’s Journey to the End of the Night. The aim of this research is to examine the aspects of existential crisis and examine the cope of existential crisis found in the Louis-Ferdinand Celine’s Journey to the End of the Night. The researcher chooses this novel because the novel depicts the issue of existential crisis through a person who live in different places with different socio-cultural context. The researcher hopes that this research can be a reference for other research conducted with the same issue, and provides understanding for the reader concerning existential crisis. The novel itself is a semi-autobiographical novel which is based on the author’s experience. The novel is written in first person point of view. The researcher focuses to examine the main character of the novel. The researcher uses a qualitative descriptive method and a psychological approach to connect existential crisis and literature. To analyze the conflict in the novel, the researcher employs Joana Butėnaitė, Jolanta Sondaitė, Antanas Mockus’s existential crisis theory to breakdown component of existential crisis. The theory is practicable in order to gain more understanding about existential crisis. For the coping of existential crisis, the researcher employs the theory by Uddin. The researcher finds all three components of existential crisis points to several aspects, namely emotional, cognitive, and behavior component. And Bardamu coping of existential crisis, namely formulating a deeper understanding of himself in his place in the world through exploring his inner thoughts. Keywords: Existential Crisis, Emotional, Cognitive, Behavior